Ultrasensitive detection and quantification of viral nucleic acids with Raindance droplet digital PCR (ddPCR) - Long, Samuel; Berkemeier, Brian (Methods (San Diego, Calif.), 2022)
•Sensitive detection of viral nucleic acids in tissue sites from infected subjects is critical for monitoring disease progression and treatment efficacy in some infectious diseases.•Protocol enables quantitative recovery of cell/tissue-associated DNA and RNA during sample preparation to preserve molecular signature representation.•Raindance ddPCR platform is used in the digital PCR step, as it was shown to allow maximizing DNA input without reaction inhibition.•RNA quantification utilizes a high processivity reverse transcriptase at the reverse transcription step, combined with Raindance ddPCR at the digital PCR step. Sensitive detection of viral nucleic acids is critically important for diagnosis and monitoring of the progression of infectious diseases such as those caused by SARS-CoV2, HIV-1, and other viruses. In HIV-1 infection cases, assessing the efficacy of treatment interventions that are superimposed on combination antiretroviral therapy (cART) has benefited tremendously from the development of sensitive HIV-1 DNA and RNA quantitation assays. Simian immunodeficiency virus (SIV) infection of Rhesus macaques is similar in many key aspects to human HIV-1 infection and consequently this non-human primate (NHP) model has and continues to prove instrumental in evaluating HIV prevention, treatment and eradication approaches. Cell and tissue associated HIV-1 viral nucleic acids have been found to serve as useful predictors of disease outcome and indicators of treatment efficacy, highlighting the value of and the need for sensitive detection of viruses in cells/tissues from infected individuals or animal models. However, viral nucleic acid detection and quantitation in such sample sources can often be complicated by high nucleic acid input (that is required to detect ultralow level viruses in, for example, cure research) or inhibitors, leading to reduced detection sensitivity and under-quantification, and confounded result interpretation. Here, we present a step-by-step procedure to quantitatively recover cell/tissue associated viral DNA and RNA, using SIV-infected Rhesus macaque cells and tissues as model systems, and subsequently quantify the viral DNA and RNA with an ultrasensitive SIV droplet digital PCR (ddPCR) assay and reverse transcription ddPCR (RT-ddPCR) assay, respectively, on the Raindance ddPCR platform. The procedure can be readily adapted for a broad range of applications where highly sensitive nucleic acid detection and quantitation are required.